2021
DOI: 10.3390/w14010056
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Removal and Woodchip Properties across a Paired Denitrifying Bioreactor Treating Centralized Agricultural Ditch Flows

Abstract: Treatment of nitrate loads by denitrifying bioreactors in centralized drainage ditches that receive subsurface tile drainage may offer a more effective alternative to end-of-pipe bioreactors. A paired denitrifying bioreactor design, consisting of an in-ditch bioreactor (18.3 × 2.1 × 0.2 m) treating ditch base flow and a diversion bioreactor (4.6 × 9.1 × 0.9 m) designed to treat high-flow events, was designed and constructed in an agricultural watershed (3.2 km2 drainage area) in Illinois, USA. Flow and water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Pfannerstill et al (2016) found nitrate concentration reductions to be more variable ranging from 7 to 41%, with an overall mean nitrate concentration reduction of 28% (8.87 to 6.43 mg L − 1 ). Maxwell et al (2022) reported the lowest mean reductions of nitrate concentrations at -1% ± 16%. Mean nitrate concentrations in the inlet and outlet were 5.9 ± 2.4 mg L − 1 and 6.1 ± 2.2 mg L − 1 , respectively.…”
Section: Quantifying Nitrogen Treatmentmentioning
confidence: 95%
See 3 more Smart Citations
“…Pfannerstill et al (2016) found nitrate concentration reductions to be more variable ranging from 7 to 41%, with an overall mean nitrate concentration reduction of 28% (8.87 to 6.43 mg L − 1 ). Maxwell et al (2022) reported the lowest mean reductions of nitrate concentrations at -1% ± 16%. Mean nitrate concentrations in the inlet and outlet were 5.9 ± 2.4 mg L − 1 and 6.1 ± 2.2 mg L − 1 , respectively.…”
Section: Quantifying Nitrogen Treatmentmentioning
confidence: 95%
“…Most of these studies focused on quantifying nitrate treatment in agricultural settings. Overall, IBRs (or in-ditch bioreactors) exhibited variability in nitrate concentration reductions ranging from -1 to 78% (Robertson and Merkley 2009;Elgood et al 2010;Pfannerstill et al 2016;Sarris and Burbery 2018;Christianson et al 2017;Maxwell et al 2022). Three of these studies (Robertson and Merkley 2009;Elgood et al 2010;Christianson et al 2017) found that nitrate concentration reductions tended to be > 50%.…”
Section: Quantifying Nitrogen Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, surface inlets, which connect ponded overland flow with the subsurface drain system via a vertical pipe, provide a direct path for surface runoff constituents (i.e., sediment) to enter the subsurface drainage system and, as a result, any linked edge-of-field practice. Sediment has been shown to shorten the lifespans of woodchip bioreactors (Christianson, et al, 2020;Duncan, 2022) and reduce the effectiveness of a woodchip bioreactor situated in an agricultural ditch (Maxwell et al, 2022a).…”
mentioning
confidence: 99%